Menjerat Kader, Melepas Partai Politik; Pertanggungjawaban Pidana Partai Politik Dalam Kasus Tindak Pidana Korupsi - Zulkifli Aspan; Wiwin Suwandi (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
Amid the resounding steps of the KPK to carry out the law enforcement function of eradicating Corruption, there are still things that feel stagnant. The KPK does not or has not dared to ensnare political parties in corrupt criminal liability, using corruption laws. In each case with dimensions of political corruption, the KPK only ensnares party elites, but does not at the same time demand criminal liability from political parties. In fact, in several cases investigated, the flow of funds flowed into political parties. As a special offense, revising the Corruption Law, by entering the phrase